EFEKTIVITAS TEKNIK RESERVE PREASURE SOFTENING DAN KOMPRES AIR HANGAT TERHADAP BENDUNGAN ASI PADA IBU POSTPARTUM - Vitria Komala Sari; Anrika Desti (Maternal Child Health Care, 2022)
SDKI data in 2018 the incidence of breast milk dam is 37.12%. Data from Pasaman Barat Health Department in 2020 as many as 26.3% of mothers with breast milk dam. One of the efforts to reduce breast milk dam is to use the Reserve Pressure Softening technique and warm water compresses. The purpose of this study was to determine the effectiveness of Reserve Preasure Softening techniques and warm water compresses on breast milk dam on postpartum mothers in the working area of Parit Community Health Center Pasaman Barat in 2022. The research design was a quasi-experimental with two group pre-post test design. The research was conducted from January to July 2022 in the Working Area of  Parit Community Health Center Pasaman Barat. The population is all post partum mothers who experience breast milk with purposive sampling technique totaling 30 people. This study used 30 respondents with 15 respondents in the reserve pressure softening technique group and 15 respondents in the warm water compress group, analyzed by univariate and bivariate analysis with independent T-test. The results of the study on the average of breast milk dam before the reserve pressure softening technique was given were 3.73 and after 2.00. The average of breast milk before being given a warm compress was 3.67 and after 3.07. The results of the statistical test showed p values of 0.000 and 0.003 that the Reserve Pressure Softening Technique was more effective than warm water compresses against breast milk dam in postpartum mothers in the Working Area of Parit Community Health Center Pasaman Barat in 2022. The conclusion of the reserve pressure softening technique was more effective than warm water compresses against the incidence breast milk dam for postpartum mothers in the working area of the Parit Community Health Center Pasaman Barat in 2022. It is hoped that the Community Health Center can apply the reserve pressure softening technique and warm water compresses for postpartum mothers with breast milk dam.